The equivalent of the given expression would be listed below as follows:
1.) 6(C+6) ---> 6c+36
2.).6c+6 ---> 2(3c+3), 3c+6+3c
3.) Neither----> 6c+12, (6*c)+(6*6), (6+c)+(6+6)
How to determine the equivalent of the given expression?
To determine the equivalent of the given expression, the following steps should be taken as follows:
Equivalents of 6(C+6):
= 6c+36 = 6(C+6)
Equivalents of 6c+6:
2(3c+3) = 6c+6
3c+6+3c = 6c+6
Equivalents of Neither:
6c+12 ≠ 6(c+6) nor 6c+6
(6*c)+(6*6) ≠ 6(c+6) nor 6c+6
(6+c)+(6+6) ≠ 6(c+6) nor 6c+6.